2010
DOI: 10.1093/pubmed/fdq036
|View full text |Cite
|
Sign up to set email alerts
|

How is diarrhoea managed in UK care homes? A survey with implications for recognition and control of Clostridium difficile infection

Abstract: This study shows that most care homes are not fully compliant with current infection prevention and control guidance, and that some unacceptable practices are occurring. In order to reduce potential for transmission of CDI and other diarrhoeal infection in care homes, infection prevention and control practices must be improved, with early diagnosis and control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…LTCFs and RCHs are being increasingly recognized as important reservoirs of C. difficile. 8 , 18 Henderson et al 19 identified significant issues regarding infection control practices in RCHs, including limited microbiological investigations, absence or delay of isolation, lack of protective equipment, inappropriate practice when cleaning the environment, and antibiotic misuse.…”
Section: Discussionmentioning
confidence: 99%
“…LTCFs and RCHs are being increasingly recognized as important reservoirs of C. difficile. 8 , 18 Henderson et al 19 identified significant issues regarding infection control practices in RCHs, including limited microbiological investigations, absence or delay of isolation, lack of protective equipment, inappropriate practice when cleaning the environment, and antibiotic misuse.…”
Section: Discussionmentioning
confidence: 99%